Coliform Contaminant Analysis at Dug Well in Ungga Village, Central Lombok District, West Nusa Tenggara - Dadan Supardan (UNIVERSITAS NEGERI PADANG, 2018)
Dug well water generally is a daily source of domestic water used by most households in Indonesia. However, the well water excavation does not meet the quality of health standards. Contamination of microorganism in dug well water occurs due to the distance of wells with septic tank, household waste disposal and animal husbandry. One of the bioindicators of contaminated groundwater is the presence of Coliform bacteria in large quantities, such as Escherichia coli, which potentially cause various diseases in human. The objective of this study was to determine the biological contamination of dug wells water in Ungga, Iting Bengkel Village, Central Lombok. This study was observational study and sampling method used purposive sampling with the number of samples was 6 dug wells. The biological contamination indicator was determined by calculating the index of Most Probable Number (MPN) Coliform. The laboratory analysis included the analysis Escherichia coli by MPN. The result showed that a total of 6 wells with distance 3.45 meters and 4.70 meters against septic tank has MPN coliform value 1898 per 100 ml. The result of water samples from 2 dug wells has contaminated by Escherichia Coli and has reached amount 14 per 100 ml (A3) and 16 per 100 ml (B3).